When food is comfort : nurture yourself mindfully, rewire your brain, and end emotional eating - Simon, Julie M., 1956- (Novato, California : New World Library, 2018)
"A guide to overcoming compulsive overeating by understanding the root psychological causes. Describes coping strategies such as developing mindful awareness of emotions and bodily sensations, practicing self-validation, and re-framing self-defeating thoughts. Contains case studies and practical exercises"--
Includes bibliographical references and index.
Keywords: Compulsive eating -- Psychological aspects; Compulsive eating -- Alternative treatment